Plastination technique, fundament and cheaper alternatives (Gaceta de Ciencias Veterinarias, 2018)
Plastination is a preserving technique of anatomical pieces based on substitution of water and lipids of tissues by a polymer such as silicone. This substitution allows to obtain a piece that lasts over time and without harmful effects for the person who uses it. This technique has four basic phases that must be met to obtain the final product, in order, these phases are fixation, dehydration, forced impregnation and curing. An important disadvantage of plastination is the high cost of production since the reagents used are produced in Germany, and must be imported by the laboratory where this technique will be performed. Additionally, necessary equipment is too expensive and has important technical specifications that must be met for safety reasons. As the research progresses, variations are emerging aimed at improving the final result and reducing the costs of producing plastinated pieces. For this reason, there are currently alternatives that allow to perform plastination in laboratories of educational institutions with limited economic resources.
Keywords: Plastination; silicone; anatomical specimens; tissues